2018
DOI: 10.3389/fphys.2018.01632
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Supplementation Improves Effort Tolerance of Rats With Hyperthyroidism

Abstract: Leucine is a regulator of protein metabolism in vivo and information on its action on effort tolerance of both animals and humans with hyperthyroidism is scarce. The objective of the present study was to verify the influence of leucine supplementation on the effort tolerance of Wistar rats with experimental hyperthyroidism. 40 animals were divided into four groups of ten: control (C), hormone (H), leucine (L), and hormone + leucine (HL). Hyperthyroidism was induced by daily administration of 20 μ⋅g100 g-1 of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…However, we observed an inverse correlation between serum FT 3 concentration and serum BTR. A study of rats with hyperthyroidism showed that leucine supplementation improved their swimming performance [23]; this suggests that thyroid hormones increase BCAA metabolism in skeletal muscle, which may be relevant to our results. Further studies are needed to elucidate the roles of thyroid hormones on BCAA metabolism in skeletal muscle.…”
Section: Discussionsupporting
confidence: 67%
“…However, we observed an inverse correlation between serum FT 3 concentration and serum BTR. A study of rats with hyperthyroidism showed that leucine supplementation improved their swimming performance [23]; this suggests that thyroid hormones increase BCAA metabolism in skeletal muscle, which may be relevant to our results. Further studies are needed to elucidate the roles of thyroid hormones on BCAA metabolism in skeletal muscle.…”
Section: Discussionsupporting
confidence: 67%
“…However, we observed an inverse correlation between serum FT 3 concentration and serum BTR. A study of rats with hyperthyroidism showed that leucine supplementation improved their swimming performance [24]; this suggests that thyroid hormones increase BCAA metabolism in skeletal muscle, which may be relevant to our results. Further studies are needed to elucidate the mechanisms of BCAA metabolism in skeletal muscle involving thyroid hormones.…”
Section: Discussionsupporting
confidence: 67%
“…However, we did observe an inverse correlation between serum FT 3 concentration and serum BTR. A study of rats with hyperthyroidism showed that leucine supplementation improved their swimming performance [30]; this suggests that thyroid hormones increase BCAA metabolism in skeletal muscle. However, the mechanisms of thyroid hormone involvement in amino acid imbalances or BCAA metabolisms have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%